Community Forestry As A Tool For Sustainable Forest Management And Rural Poverty Reduction In Cambodia - Ty, Sokhun (2011)
As deforestation and forest degradation continue, the trend of managing the forest has advanced from centralized or state managed to decentralized and community-based management. Innovative approaches, such as community forestry (CF), play an important role in supporting livelihood and the sustainable forest management. Community Forestry (CF) was launched in Cambodia to address the growing poverty in the rural areas. The pro-poor approach in forest resource management aims to provide security of tenure to the communities over the resources they are managing. The CF is expected to address the growing land conflicts in the hinterlands.